Short stories and political philosophy power, prose, and persuasion - Dolgoy, Erin A.; Hale, Kimberly Hurd, 1983-; Peabody, Bruce Garen, 1969- (Politics, literature, & film., 2019)
"This book examines the intersection of fictional narratives and political philosophy, focusing specifically on the use of short stories to teach the classic works of political philosophy. It is a resource for scholars and teachers of politics, philosophy, and literature"--